2005
DOI: 10.1111/j.1572-0241.2005.41081.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CCK-1 Antagonist, Dexloxiglumide, in Female Patients with Irritable Bowel Syndrome: A Pharmacodynamic and Pharmacogenomic Study

Abstract: Dexloxiglumide accelerates gastric emptying and delays proximal but not overall CT in patients with C-IBS. Dexloxiglumide does not accelerate transit in C-IBS. The role of CCK-1 gene polymorphisms in delaying gastric emptying and in determining response to therapy deserves further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 46 publications
2
47
0
Order By: Relevance
“…Loxiglumide also failed to alter the interdigestive colonic motor activity in the left side of the colon suggesting that the predominant action of CCK was in the ascending colon. In healthy volunteers, CCK 1 receptor antagonists have consistently accelerated colonic transit [32,86,89] , but no acceleration was seen after a short-term treatment of either unselected IBS patients or C-IBS patients [90,91] . Both studies showed that the CCK 1 antagonists loxiglumide and dexloxiglumide signifi cantly delayed proximal colonic transit and this effect could be attributed to reduced emptying from the ascending colon.…”
Section: Functional Gastrointestinal Disorders (Dyspepsia Irritable mentioning
confidence: 99%
“…Loxiglumide also failed to alter the interdigestive colonic motor activity in the left side of the colon suggesting that the predominant action of CCK was in the ascending colon. In healthy volunteers, CCK 1 receptor antagonists have consistently accelerated colonic transit [32,86,89] , but no acceleration was seen after a short-term treatment of either unselected IBS patients or C-IBS patients [90,91] . Both studies showed that the CCK 1 antagonists loxiglumide and dexloxiglumide signifi cantly delayed proximal colonic transit and this effect could be attributed to reduced emptying from the ascending colon.…”
Section: Functional Gastrointestinal Disorders (Dyspepsia Irritable mentioning
confidence: 99%
“…13 Selective CCK 1 receptor antagonism by dexloxiglumide (DEX), has been shown to improve functional gut symptoms both in the context of mechanistic studies as well as randomized clinical therapeutic clinical studies in patients with IBS. 14,15 Our aim was to demonstrate the mechanism of this effect, specifically, whether CCK 1 receptor antagonism enhances gas transit and tolerance in patients with FGD using as an experimental model the gas plus lipid challenge test.…”
Section: Introductionmentioning
confidence: 99%
“…Using radio-opaque markers to measure colon transit, the bulking agent calcium carbophil was found to prolong colon transit time in diarrhoea-predominant (IBS-D) patients, but reduce colon transit time in constipation-predominant (IBS-C) patients, compared to a drug-free baseline condition. The cholecystokinin-1 antagonist dexloxiglumide slowed ascending colon emptying (and accelerated gastric emptying) as measured by scintigraphy, but had no effect on overall colon transit time compared to placebo in 36 women with IBS-C [44] . Colon transit time positively correlated with the composite score of bowel function (i.e.…”
Section: Predictive Validity Of Gi Transit Studies For Ibs Drug Develmentioning
confidence: 99%